2020
DOI: 10.5964/meth.2807
|View full text |Cite
|
Sign up to set email alerts
|

The inaccuracy of sample-based confidence intervals to estimate a priori ones

Abstract: Confidence intervals (CIs) constitute the most popular alternative to widely criticized null hypothesis significance tests. CIs provide more information than significance tests and lend themselves well to visual displays. Although CIs are no better than significance tests when used solely as significance tests, researchers need not limit themselves to this use of CIs. Rather, CIs can be used to estimate the precision of the data, and it is the precision argument that may set CIs in a superior position to signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Unfortunately, misunderstandings of CIs are not uncommon, and further guidance regarding their use and interpretation is still needed (Belia et al, 2005;Cumming & Calin-Jageman, 2017;Fidler et al, 2004;Morey et al, 2016). Namely, asking how much and how uncertain are the salient statistical literacy (Calin-Jageman & Cumming, 2019;Trafimow, 2018;Trafimow & Uhalt, 2020). In particular, it should be noted that the sample size calculation for constructing CIs may be different from those for testing hypotheses (Borenstein et al, 2001) because the expected width or precision is the concern, rather than the statistical power (Kelley et al, 2003).…”
mentioning
confidence: 99%
“…Unfortunately, misunderstandings of CIs are not uncommon, and further guidance regarding their use and interpretation is still needed (Belia et al, 2005;Cumming & Calin-Jageman, 2017;Fidler et al, 2004;Morey et al, 2016). Namely, asking how much and how uncertain are the salient statistical literacy (Calin-Jageman & Cumming, 2019;Trafimow, 2018;Trafimow & Uhalt, 2020). In particular, it should be noted that the sample size calculation for constructing CIs may be different from those for testing hypotheses (Borenstein et al, 2001) because the expected width or precision is the concern, rather than the statistical power (Kelley et al, 2003).…”
mentioning
confidence: 99%
“…This last is unknown. In addition, Trafimow and Uhalt (2020) have shown that sample confidence intervals tend to be inaccurate representations of population confidence intervals unless sample sizes are much larger than those typically employed. An alternative way to address the issue is to use the a priori procedure (APP) that has been employed previously in a variety of ways not pertaining to Cohen's d (e.g.…”
mentioning
confidence: 99%
“…In contrast, however, Trafimow (2018b) has shown that confidence intervals are problematic in that they confound three kinds of precision. Trafimow and Uhalt (in press) demonstrated that traditional confidence intervals based on samples are very poor estimates of population intervals unless sample sizes are ridiculously large. Therefore, traditional confidence intervals are not useful either.…”
mentioning
confidence: 99%